Development of non-destructive small specimen creep testing techniques - Ali, Balhassn S. M. (2014)
Having knowledge of the current creep strength of service-aged components in high temperature installations such as nuclear power stations, oil refineries and chemical plants is essential for their safe and economic operation. Obtaining this knowledge may involve the use of small material samples. These small samples may be removed from weld regions or from component surfaces. Improving small specimens creep testing techniques, whereby a reliable uniaxial minimum strain rate and rupture data can be obtained, has been a major engineering concern for the last 20 years or so.